Análise do efeito da duloxetina no crescimento de tumor de Ehrlich em camundongos. Estudo randomizado, encoberto - Moura, Ed Carlos Rey [UNIFESP] (2017)
Background and Objectives: Adjuvants may promote analgesic effect and reduce the amount of opioids required in the treatment of cancer pain. The aim of the study was to analyze whether duloxetine, used in the treatment of cancer pain, has a direct influence on growth of the Ehrlich tumor inoculated in mice. Method: A total of 40 mice were divided into 4 groups, and 5 of each group were evaluated for survival. Mice received 5 (D5 group), 10 (D10), 30 mg / kg (D30) duloxetine or saline solution (C). The following were evaluated: survival; volume of ascites; abdominal circumference; living tumor cells in the ascites; hemogram; leukocytes in the ascites, lymph nodes, bone marrow; cytokines (interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), interleukins (IL) 6, 10, 17; monocyte chemotactic protein, (MCP); nitrite and nitric oxide (NO) in ascites and spleen; arginase, superoxide dismutase (SOD) in ascites, immunophenotyping of the spleen. Results: There was no difference in survival, weight, abdominal circumference, ascites volume, and number of tumor cells in ascites. There was no difference in leukocytes in the spleen. The number of leukocytes in mesenteric lymph node was higher with duloxetine; in the bone marrow was higher with 10 and 30 mg / kg. The number of GV was lower in D5 and D10 and hemoglonia was lower in D5; GB did not change with duloxetine; the platelet count was lower with duloxetine 10 and 30mg / kg. TNF-α in ascites was lower with 10mg / kg; serum IFN-γ was lower at 30mg / kg; IL6 in the spleen was lower at 5mg / kg; and IL17 in the spleen was greater at 30mg / kg. NO in the spleen was higher with 30mg / kg; in the ascites was lower with 10mg / kg. SOD in ascites was higher with 5 and 10 mg / kg. Antibody for CD3 was lower at 5 and 10mg / kg; for CD4 was lower with 5 and 30mg / kg; for CD8 was lower with 5mg / kg; or CD28 was lower with 5 and 30mg / kg. Conclusions: Duloxetine may play a role in tumor growth, as evidenced by anemia, by the reduction of CD4 + T cells, CD8 + T cells and their activation in the spleen, and by the pattern of cytokines that characterize an M2 macrophage pattern.